STAGES OF DEVELOPMENT OF PROFESSIONAL LEXICAN LINGUISTICS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the historical stages of formation and development of professional lexis in Uzbek linguistics. Professional lexis, as a system of terms and concepts related to a specific field of activity, is considered an important indicator of the development of a literary language. The study identifies five main stages: the early 20th century (Arabic and Persian terms), 1930–1950 (Russian and international terminology), 1960–1980 (internal lexical-semantic enrichment), 1990–2010 (national terminology formation), and 2020–present (digital Turkology and artificial intelligence). The relevance of the research is determined by the need to systematize terminological processes in the context of globalization and digitalization. The article also analyzes modern trends such as corpus-based terminology management, English borrowings, and standardization efforts. The findings contribute to the further development of Uzbek terminological schools and can be used in lexicographic practice and computational linguistics.